Implementasi LKPD Berbasis STEM untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Safiratul Fithri; Andi Ulfa Tenri Pada*; Wiwit Artika; Cut Nurmaliah; Hasanuddin Hasanuddin (Jurnal Pendidikan Sains Indonesia, 2021)
The learning process only focuses on the material by memorizing concepts, students have not utilized worksheets to do practical work optimally, so the biology learning process in schools does not encourage students to practice critical thinking skills. This study aimed to determine the effect of implementing STEM-based student worksheets in improving students' critical thinking skills at SMP Negeri 1 Peusangan, Bireuen Regency. This study used a pretest-posttest control group design. The study population was 88 VIII grade students of SMP Negeri 1 Peusangan. The research sample consisted of 67 students. The sample is determined through the purposive sampling technique. The researcher determines the class of the research sample using purposive sampling. The taking of the experimental class and the control class is determined by looking at the standard deviation of the results of the homogeneous pretest of students (the ability of homogeneous students). Critical thinking skills are measured by multiple-choice questions with reason. It is used to determine the increase and difference in the critical thinking skills of students. Analysis of N-Gain test data, paired sample t-test, and independent sample t-test. The results showed that the implementation of STEM-based LKPD could improve students' critical thinking skills on excretory system material in class VIII of SMP Negeri 1 Peusangan. In addition, there are differences in the KBK of students between the experimental class and the control class on the excretory system concept in class VIII of SMP Negeri 1 Peusangan.